Dependent Rational Activists: Disability, Student Activism, and Special Education - Dhingra, Neil; Miller, Joel (Philosophical Inquiry in Education, 2021)
Historians of student activism have rarely focused on students with disabilities, while educational historians who study students with disabilities have focused on legal reforms, not activism. We present a philosophical argument for an inclusive definition of student activism that can take place within legal and bureaucratic processes in which students act collaboratively with parents or guardians. Drawing on the new disability history and critical disability studies, we first argue that such activism is necessary because those processes routinely involve the conceptual objectification, silencing, and invisibilization of disabled people. Further, we argue that activism is necessary to shift individualized education plan (IEP) meetings from bargaining to collective deliberations for the common good. Finally, following Alasdair MacIntyre, we argue that activism, legal and otherwise, may involve families acting collaboratively, because parents and others can become attentive to the rational reflections of those with disabilities.